Smarter Money: How AI is Transforming Everyday Finance for Individuals and Businesses - Ravishankar, Srinivasan (International Journal of Computing and Engineering, 2025)
The integration of Artificial Intelligence into financial operations has revolutionized traditional banking and financial management models, opening up unprecedented opportunities for both individuals and businesses. This transformation extends beyond conventional algorithmic trading to reshape everyday financial tasks, from personal budgeting to enterprise-level risk management. AI-powered systems have demonstrated impressive capabilities in transaction processing, fraud detection, and regulatory compliance, while also reducing operational costs and improving accuracy rates. Personal finance applications now leverage machine learning to deliver personalized budgeting solutions and optimize bill payments, while businesses benefit from enhanced accounting automation and advanced payroll management systems. The use of AI in credit risk assessment and fraud prevention has significantly strengthened security across financial institutions. These advancements point to a future in which AI functions not merely as an automation tool, but as a strategic partner in financial decision-making—fundamentally transforming how individuals and organizations manage their financial activities.